Acoustic Neuroma Mimicking Orofacial Pain: A Unique Case Report. (7th December 2016) - Ramdurg, Praveenkumar; Srinivas, Naveen; Mendigeri, Vijaylaxmi; Puranik, Surekha R.
Abstract : Acoustic neuroma (AN), also called vestibular schwannoma, is a tumor composed of Schwann cells that most frequently involve the vestibular division of the VII cranial nerve. The most common symptoms include orofacial pain, facial paralysis, trigeminal neuralgia, tinnitus, hearing loss, and imbalance that result from compression of cranial nerves V–IX. Symptoms of acoustic neuromas can mimic and present as temporomandibular disorder. Therefore, a thorough medical and dental history, radiographic evaluation, and properly conducted diagnostic testing are essential in differentiating odontogenic pain from pain that is nonodontogenic in nature. This article reports a rare case of a young pregnant female patient diagnosed with an acoustic neuroma located in the cerebellopontine angle that was originally treated for musculoskeletal temporomandibular joint disorder.